PENERAPAN KESELAMATAN DAN KESEHATAN KERJA DALAM UPAYA MENGURANGI ANGKA KECElAKAAN (KASUS PADA PROYEK SKYLINE TOWERS CONDOTEL & OFFICE) - Pratiwi Isnaeni; Demes Nurmayanti; Sukiran Al Jauhari (Poltekkes Kemenkes Surabaya, 2014)
The implementation of occupational safety and health principles was conducted by establishingpolicies, planning and its implementation, monitoring and evaluating occupational safety and healthperformances, as well as reviewing and improvement of that performances. The aim of this study was toevaluate the implementation of the principles of occupational safety and health in order to reduce accidentrates among construction workers at construction site of the Skyline project in Surabaya.This was an observational study with cross sectional approach. Data were collected by means ofinterviews and observations using a check list. The number of population was 535 and the sample consistedof 84 construction workers and 6 staffs of occupational safety and health committee which were drawnrandomly. Data obtained were analyzed descriptively using tabulation and interpretation.The results showed that majority of respondents aged 40 years (77,38%), duration ofemployment 1-5 years (52,38%), and their educational level were elementary and junior high school(48,81%). These respondents have adequate knowledge in safety and health principles. Occupationalsafety and health has been adequately practiced.Based on the results of this study it can be concluded that the occupational safety and health inthis company had been adequately implemented. It is recommended to this company to maintain anduphold its occupational safety and health programs.